2013
DOI: 10.2116/analsci.29.143
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Japanese Polished Rice by Stable Hydrogen Isotope Analysis of Total Fatty Acids for Tracing Regional Origin

Abstract: We determined the δD values of the total fatty acids of Japanese rice to test the hypothesis that there is a wide variation in the hydrogen isotopic composition (δD) of the total fatty acids of Japanese rice sourced from different growth areas in Japan and to distinguish the minor differences among these growth areas. The δD values showed a wide variation ranging from -216 (Hokkaido) to -183 (Okinawa), indicating a good correlation with the corresponding variations for ambient water (r = 0.63) and mean tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…On the other hand, the δD and δ 18 O of brewer's alcohol may differ from the native alcohol of unadulterated sake. Because the δD and δ 18 O of organic plant matter are responsive to the isotopic values of the water in the area in which it is grown, 18,19) brewer's alcohol derived from plant carbohydrates has the potential to directly reflect isotopic changes in the plant's origin. Thus, a difference in the δD and δ 18 O in a plant's origin could be useful for detecting brewer's alcohol in sake.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…On the other hand, the δD and δ 18 O of brewer's alcohol may differ from the native alcohol of unadulterated sake. Because the δD and δ 18 O of organic plant matter are responsive to the isotopic values of the water in the area in which it is grown, 18,19) brewer's alcohol derived from plant carbohydrates has the potential to directly reflect isotopic changes in the plant's origin. Thus, a difference in the δD and δ 18 O in a plant's origin could be useful for detecting brewer's alcohol in sake.…”
mentioning
confidence: 98%
“…Further complicating matters, Baudler et al 20) reported that the isotopic values of the distillate were different between the first and last fractions in a distillation process for concentrating and purifying ethanol. While there are a number of studies using δD or δ 18 O to analyze ethanol in alcoholic beverages via gas chromatography-high-temperature conversion-isotope ratio mass spectrometry (GC-TC-IRMS) using the headspace solid-phase microextraction method, the separation of ethanol is relatively complicated and time consuming. 13,21) Measurement via analysis of δD and δ 18 O in bulk alcoholic beverages may have the advantage of quickly screening for alcohol addition without separation of the ethanol (i.e., even in the presence of water and H/O-containing non-volatile components such as sugars).…”
mentioning
confidence: 99%
See 3 more Smart Citations